Intelligent Biosignal Analysis Methods - Jović, Alan (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book describes recent efforts in improving intelligent systems for automatic biosignal analysis. It focuses on machine learning and deep learning methods used for classification of different organism states and disorders based on biomedical signals such as EEG, ECG, HRV, and others.